Enantioselective Suzuki cross-coupling of 1, 2-diboryl cyclopropanes. Issue 6 (23rd January 2023) - Teresa, Javier; Velado, Marina; Fernández de la Pradilla, Roberto; Viso, Alma; Lozano, Blanca; Tortosa, Mariola
Abstract : The catalytic enantioselective desymmetrization of 1, 2-bis-boronates through a Suzuki–Miyaura cross coupling provides a powerful tool for the preparation of enantioenriched cyclopropyl boronates. Abstract : Herein, we describe the catalytic enantioselective cross-coupling of 1, 2-bisboronic esters. Prior work on group specific cross coupling is limited to the use of geminal bis-boronates. This desymmetrization provides a novel approach to prepare enantioenriched cyclopropyl boronates with three contiguous stereocenters, that could be further derivatized through selective functionalization of the carbon–boron bond. Our results suggest that transmetallation, which is the enantiodetermining step, takes place with retention of stereochemistry at carbon.